Opportunities and Challenges of Halal Certification in Micro, Small and Medium Food Enterprises (MSMEs) in Bandung - Juliana, Juliana; Revinda, Relly; Al Adawiyah, Rumaisah Azizah; Manne, Firman; Umar, Abdurrauf; Oroji, Ahamad Muhammad (Perhimpunan Intelektual Muslim Indonesia, 2024)
The purpose of this study was to knowing and analyzing the halal certification strategy in Greater Bandung with the IFAS and EFAS matrices based on expert judgment surveys. The method used in this research is a qualitative method with a descriptive research design. The analytical tools used are the IFAS matrix (Internal Strategic Analysis Summary) and the EFAS matrix (External Strategic Factors Analysis Summary). The results of the study show that the internal external matrix (IE) is in quadrant I with growth conditions. Stakeholders in Raya Bandung need to make efforts to improve halal certification. Several efforts that can be made by stakeholders are increasing awareness of the importance of halal certification so that they can help each other and support the implementation of halal certification in Greater Bandung. This research is the first to analyze the halal certification strategy for MSMEs in Greater Bandung.